Assessment of functional impairment in patients with chronic non-specific low back pain depending on the dominant type of pain - Kondratiuk, Mykola; Ovdii, Mariia (The Ukrainian Scientific Medical Youth Journal, 2025)
Chronic non-specific low back pain is a musculoskeletal disorder that has a significant tendency to spread among working-age people throughout their lives worldwide. Lower back pain is the leading cause of disability worldwide among people of working age and is a significant social and economic burden on the healthcare system. In patients with chronic low back pain, assessment of functional impairment is of important clinical significance, as it allows for evaluation of the complexity of the course, the effectiveness of treatment, and the prognosis for the disease. To assess the degree of functional impairment in patients with chronic non-specific low back pain depending on the dominant type of pain. A retrospective single-center pilot study was conducted and included patients with chronic non-specific low back pain who underwent rehabilitation in the rehabilitation department of the Bogomolets National Medical University. All participants were divided into three groups depending on the dominant type of pain: with a predominance of nociplastic pain, with a predominance of neuropathic pain, and with a predominance of nociceptive pain. The subjects underwent an assessment of socio-demographic and anthropometric indicators, pain status, and functional impairment using the Oswestry Disability Index (ODI) questionnaire, and subjective assessment of stress level (PSS-10). Among 102 subjects with chronic non-specific low back pain, 63% were women and 37% were men of working age, with a mean age of 39.0±12.3 and 40.4±10.5 years, respectively. Among the subjects, nociceptive pain was dominant in 53.9% (CI 44.1-63.6%), nociplastic pain was present in 22.5% (CI 14.9-31.2%), 15.7% (CI 9.2-23.4%) had neuropathic pain, and in 7.8% (CI 3.4-13.9%) of the subjects, the dominant type of pain could not be determined. In the group of patients with a dominant nociplastic type of pain, the ODI dysfunction index was 27.2±14.0%, which corresponds to moderate dysfunction. In the group with a dominant neuropathic type of pain, this indicator was 22.0±12.1%, which also indicates moderate impairment. Among patients with nociceptive type of pain, the ODI indicator corresponded to minimal impairment, 13.6±10.7%, the difference was significant compared to the group of patients with dominant nociplastic and neuropathic pain, respectively (p<0.001, p=0.009). Most patients with chronic non-specific low back pain with a dominant nociplastic type of pain have moderate functional impairment. In this group of patients, low back pain most significantly limits functioning during sitting, standing, social and sexual life, and traveling. Most patients with nociceptive and neuropathic type of pain have minimal functional impairment.